The Northeast Greenland Shelf as a Potential Habitat for the Northeast Arctic Cod - Strand, Kjersti O.; Sundby, Svein; Albretsen, Jon; Vikebø, Frode B. (Frontiers in Marine Science, 2017)
Observations (1978-1991) of distributions of pelagic juvenile Northeast Arctic cod (Gadus morhua L.) show that up to 1/3 of the year class are dispersed off the continental shelf and into the deep Norwegian Sea while on the way from the spring-spawning areas along the Norwegian coast to the autumn-settlement areas in the Barents Sea. The fate of this variable fraction of pelagic juveniles off-shelf has been an open question ever since Johan Hjort’s (1914) seminal work. We have examined both the mechanisms causing offspring off-shelf transport, and their subsequent destiny using an individual-based biophysical model applied to quantify growth and dispersal. Our results show, consistently with the observations, that total off-shelf transport is highly variable between years and may be up to 27.4 %. Offspring from spawning grounds around Lofoten have a higher chance of being displaced off the shelf. The off-shelf transport is dominated by episodic events where frequencies and dates vary between years. Northeasterly wind conditions over a 3-7-day period prior to the off-shelf events are a good proxy for dispersal of offspring off the shelf. Offspring transported into the open ocean are on average carried along three following routes: back onto the adjacent eastern shelves and into the Barents Sea (36.9 %), recirculating within the Lofoten Basin (60.7 %), or drifting northwest to the northeast Greenland shelf (2.4 %). For the latter fraction the transport may exceed 12 % depending on year. Recent investigations have discovered distributions of young cod on the northeast Greenland shelf indicating that conditions may support survival for NEA cod offspring.